Effect of inulin on the pasting and retrogradation characteristics of three different crystalline starches and their interaction mechanism - Ji, Xiaolong; Wang, Zhiwen; Jin, Xueyuan; Qian, Zhenpeng; Qin, Le; Guo, Xudan; Yin, Mingsong; Liu, Yanqi (Frontiers in Nutrition, 2022)
In this paper, three different crystalline starches (wheat, potato and pea starch) were compounded with natural inulin, and its pasting, retrogradation and structure were investigated. And then, the potential mechanism of interaction between inulin and starch was studied. Results showed that there were some differences in the effects of inulin on the three crystalline starch. Pasting experiments showed that the addition of inulin not only increased pasting viscosity but also decreased the value of setback and breakdown. Retrogradation experiment dates demonstrated that inulin delayed gelatinization of all three starches. Inulin could reduce the enthalpy of gelatinization and retrogradation to varying degrees, and inhibit the retrogradation of starch. Among them, it had a better inhibitory effect on potato starch. X-ray diffraction revealed that inulin interacted mainly with the leached amylose. Fourier-transform infrared spectroscopy and interaction force experiments results showed that inulin interacts with amylose through hydrogen bonding and observed the presence of electrostatic force in the complexed system. Based on the above experimental results speculate that the mechanism interaction of between inulin and three crystalline starches were the same, and the difference in physicochemical properties was mainly related to the ratio of amylose to amylopectin in different crystalline starches. These findings could enrich the theoretical system of the inulin with starch compound system and provide a solid theoretical basis for further applications.